(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2022)
As a result of the determination of the physico-chemical indicators of various toothpastes, their compliance with the regulatory requirements of the hydrogen indicator was observed, the content of the spirit in the composition of one sample in terms of the amount of turn metals has a high value.